2007
DOI: 10.1017/s1092852900015467
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors for Suicidal Ideation and Behaviors in Obsessive-Compulsive Disorder

Abstract: Suicidality has been underestimated in OCD and should be investigated in every patient, so that appropriate preventive measures can be taken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 25 publications
2
18
0
3
Order By: Relevance
“…This finding is in accordance with the work of Torres et al, 27 who reported that depressive symptoms were associated with previous suicidal ideation but not with current suicidal ideation or with suicide attempts. Apter et al 28 even found an inverse relationship between depression and suicidal behavior in a sample of adolescents with OCD.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in accordance with the work of Torres et al, 27 who reported that depressive symptoms were associated with previous suicidal ideation but not with current suicidal ideation or with suicide attempts. Apter et al 28 even found an inverse relationship between depression and suicidal behavior in a sample of adolescents with OCD.…”
Section: Discussionsupporting
confidence: 93%
“…Reported variables had a percentage of missing data ranging from 0 to 22%. with rates of SA between 3 and 27% in OCD patients, 4,[28][29][30][31][32] also considering the most recent Brazilian and Swedish reports documenting rates of 11.7 and 19.4%, respectively. 6,7 It is also noteworthy that, in the present study, significantly higher rates of SA history were reported in OCD patients from Europe and South Africa (40 and 39%, respectively) compared to those from North America and the Middle East (13 and 8%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…rates of comorbid depression and anxiety rather than OCD itself [10,11], but controlling for comorbidity the risk of suicidality remains substantial among OCD sufferers (de la Cruz et al, 2016). In general, studies have reported high rates of suicidal ideation in OCD ranging between 20% and 46% [11][12][13][14][15]. Another recent study reported that 65% of the OCD patients had endorsed at least one of the questions about suicidal phenomena as positive.…”
Section: Introductionmentioning
confidence: 99%